Chemical and Biological Weapons : The Interconnectivity of Norms - Vries, Barry de (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2026)
The bans on chemical and biological weapons, upheld by the Chemical Weapons Convention (CWC) and the Biological Weapons Convention (BWC), are foundational to global disarmament and international security. However, these regimes are under increasing strain due to recent violations, such as chemical attacks in Syria and targeted poisonings in Europe, as well as allegations linked to the ongoing conflict in Ukraine. Furthermore, broader institutional challenges are undermining arms control efforts. This book seeks to strengthen the norms against chemical and biological weapons by offering in-depth insight into the interconnectivity of international, domestic, and professional norms that support and enforce these prohibitions.